2019
DOI: 10.1016/j.sjbs.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of the methanolic extract of Lepidium sativum seeds on mice infected with Trypanosoma evansi

Abstract: The present study aimed to investigate the therapeutic potential of the methanolic extract of Lepidium sativum seeds in mice experimentally infected with Trypanosoma evansi. A total of thirty-two male Swiss albino mice were randomly divided into four groups: the first group was the normal control, while the second, third and fourth groups were infected intraperitoneally with 1 × 104 trypanosomes. The third and fourth groups were treated with 100 μl of Lepidium sativum seed extract (LSSE) at a dose of 200 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
6
5
0
Order By: Relevance
“…But the rate of increment in parasitemia level was signi cantly very low (P < 0.05) compared with that of the controls. The present study results are in agreement with those of the previous study by Al-Otaibi et al, (10), which reported antitrypanosomal activity of L. sativum against T. evansi. The antitrypanosomal activity of the extract might be attributed to its antioxidant and/or its immune boosting properties (10).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…But the rate of increment in parasitemia level was signi cantly very low (P < 0.05) compared with that of the controls. The present study results are in agreement with those of the previous study by Al-Otaibi et al, (10), which reported antitrypanosomal activity of L. sativum against T. evansi. The antitrypanosomal activity of the extract might be attributed to its antioxidant and/or its immune boosting properties (10).…”
Section: Discussionsupporting
confidence: 94%
“…Lepidium sativum 'Fetto' in Amharic is also among the plants claimed to have antiprotozoal activity and/or antitrypanosomal effect in particular. A single dose in vivo test reported by Al-Otaibi et al, (10) concluded that the plant extract had antitrypanosomal activity against T. evansi. Therefore, the present study was targeted to investigate the in vivo antitrypanosomal activity of crude extracts of leaves of C. citratus and seeds of L. sativum at a variable concentration.…”
Section: Introductionmentioning
confidence: 98%
“…But the rate of increment in parasitemia level was significantly very low ( P < 0.05) compared with that of the controls. The present study results are in agreement with those of the previous study by Al-Otaibi et al [ 14 ], which reported antitrypanosomal activity of L. sativum against T. evansi . Unlike the previous study that used single dose and fixed administration and the follow up periods were only for 4 days, the present study tried to show the effect of the extract in variable dose ranges and longer follow-up period (14 days) by considering the undulating nature of the level of parasitemia in the body of animals.…”
Section: Discussionsupporting
confidence: 94%
“…Lepidium sativum ‘Fetto’ in Amharic is also among the plants claimed to have antiprotozoal activity and/or antitrypanosomal effect in particular. A single dose in vivo test reported by Al-Otaibi et al, [ 14 ] concluded that the plant extract had antitrypanosomal activity against T. evansi . Therefore, the present study was targeted to investigate the in vivo antitrypanosomal activity of crude extracts of leaves of C. citratus and seeds of L. sativum at a variable concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that infection with T. evansi induced leukopenia and this was enhanced by treatment with methanol extract. Leukocytosis, which was recorded in our study, is a good indicator of enhancement and strengthening of the immune system by increasing the mean production of WBCs [ 34 ] and increasing mononuclear phagocytic system activity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%